2009
DOI: 10.2310/jim.0b013e31819d87c1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA Damage and Antioxidant Defense after Reperfusion in Acute Myocardial Infarction

Abstract: Although not correlated with other cardiac markers, plasma level of 8-OHdG shows a decrease after reperfusion therapy in patients with MI, and primary percutaneous transluminal coronary angioplasty seems much more effective than thrombolytic therapy for providing a low level of 8-OHdG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…The decreased MDA levels indicated the improvement of the pro-and antioxidant balance in the SAP patients, probably due to the reduction in the number of ischemic events. These observations are consistent with the results of other studies [38,44,54,55]. Bashar and Akhtan [38] demonstrated that the regular treatment of AMI patients led to a significant decrease in oxidative stress parameters.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The decreased MDA levels indicated the improvement of the pro-and antioxidant balance in the SAP patients, probably due to the reduction in the number of ischemic events. These observations are consistent with the results of other studies [38,44,54,55]. Bashar and Akhtan [38] demonstrated that the regular treatment of AMI patients led to a significant decrease in oxidative stress parameters.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, a more advanced state of atherosclerosis was associated with a greater pro-and antioxidant imbalance. Thus, the level of oxidative stress may be used as an independent predictor of cardiovascular events, in agreement with the observations of other authors [15,40,41,[43][44][45][46][47]. Blankenberg et al [43] found an inverse association between erythrocytic GSH-Px and the risk of cardiovascular events.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, immunoassays for measurement of 8-OHdG and F2-isoP have been criticized, although results employing this technology being widely published. [26][27][28] Recent publications critiquing ELISA-based 8-OHdG methods suggest that ELISA-based values tended to be higher values than ''gold-standard'' LC/ MS-based measurement. 29 However, several steps were taken in this trial protocol to reduce sources of variability that should have improved the ability to detect a trend for change, if one was present.…”
Section: Figmentioning
confidence: 99%